(Ef)Facing the Face of Nationalism: Wrestling Masks in Chicano and Mexican Performance Art - Robert Neustadt (Studies in 20th & 21st Century Literature, 2001)
Masks serve as particularly effective props in contemporary Mexican and Chicano performance art because of a number of deeply rooted traditions in Mexican culture. This essay explores the mask as code of honor in Mexican culture, and foregrounds the manner in which a number of contemporary Mexican and Chicano artists and performers strategically employ wrestling masks to (ef)face the mask-like image of Mexican or U.S. nationalism. I apply the label "performance artist" broadly, to include musicians and political figures that integrate an exaggerated sense of theatricality into their performances. Following the early work of Roland Barthes, I read performances as "texts" in which the wrestling masks function as immediately recognizable signs. I argue that by masking their identity and alluding to popular mask traditions, Chicano and Mexican performance artists make visible, and interrogate, the national face(s) of power.
Keywords: nationalism; Chicano; Mexican; performance art; contemporary performance; tradition; culture; wrestling masks; U.S.; face; power; identity; sign